Techniques of Xhosa music: a study based on the music of the Lumko district - Dargie, David John (Rhodes University, Faculty of Humanities, Department of Music, 1987)
Part 1.Thesis: Chapter 1: The people of the Lumko district (the villages of Ngqoko and Sikhwankqeni) are AbaThembu, mostly of the Gcina clan cluster. Their history has caused them to be linked with (now vanished) San peoples in special ways, which have undoubtedly influenced their music. Chapter 2: The music of these people is centred around their religious and social life. This affects the way they classify their songs; and song classifications (and the way songs are used) affect their performance, in particular, the dance styles associated with the song classes. Chapter 3: A variety of musical instruments is used in the Lumko district, the most important being the musical bows. Once again, the use of these bows gives an insight into the musical influences that have affected the people historically. The ways the bows work are described, as well as ways to play them. Chapter 4: Overtone singing, not previously documented anywhere in traditional African music, is practised in certain ways by these AmaGcina. These, and other vocal techniques, are described. Chapter 5: From the terminology and the methods of conceptualisation about music in the Lumko district, it is possible to gain an insight into a truly Xhosa technical understanding of Xhosa music. Once again a historical insight is gained, because so many of the important terms are KhoiSan words. Chapter 6: A Western technological (i. e. musicological) understanding of the music is also necessary in a study of this nature. This chapter applies musicological concepts to an examination of the relationship between speech and song, of the usages in melody and scale, harmony theory, rhythm, polyphony, song form, instrumental roles and methods of performance. Chapter 7: This is the conclusion of the thesis. It sums up what has been studied: musical techniques, principles, the importance of Ntsikana 's song as a basis for musical comparisons, and the import of the historical aspects of the study - a possible glimpse of the music of the San. PART 2. MUSIC TRANSCRIPTIONS AND DESCRIPTIONS. The transcriptions of 62 songs provide the material for this study. The songs were chosen to represent all the major song classes used in the Lumko district, and to represent all the important music techniques as well. The songs are in fifteen categories. Each song is accompanied by its technical details, and sufficient commentary to make the song transcription intelligible and meaningful. Certain key songs are chosen as type-songs or other special examples, and are used as the bases for discussion on song style characteristics, principles of performance, bow adaptation, and so on. A general Introduction to Part 2 describes and accounts for the method of transcription, and also attempts to make it possible for the score reader not only to analyse, but also to perform the songs. In a further attempt to bring the transcriptions to life, a video recording of certain key songs and techniques, and audio tapes with examples taken from all the songs, accompany this study
Keywords: Xhosa (African people) -- Music; Lumko district; Eastern Cape (South Africa); Xhosa music; Musicology; AbaThembu; Ntsikana; Songs; Musical bows; Overtone singing